Systematic proteomics analysis of lysine acetylation reveals critical features of renal proteins in kidney calculi formation - Shiwei Zhang; Zhu Wang; Hao Jiang; Jieyan Wang; Meiyu Jin; Hui Liang; Qiong Deng (PLoS ONE, 2026)
In this study, we systematically integrated proteome and acetyl proteome (acetylome) approaches to investigate the characteristics of renal proteins in a CaOx crystal rat model. We aimed to understand the pathogenesis of kidney calculi and delineate the landscape of acetylation within kidney calculi, potentially leading to the identification of valuable and novel biomarkers. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), we analyzed the protein expression profiles and lysine acetylation (Kac) features in kidney tissues obtained from rats with kidney calculi and those without (normal controls). Our results revealed 118 downregulated and 129 upregulated proteins. Furthermore, we identified 538 upregulated Kac sites in 258 proteins and 133 downregulated Kac sites in 118 proteins between kidney calculi and paired normal rats. Functional enrichment and protein-protein interaction network analyses revealed that the mitochondria were the most abundant acetylated protein fraction, and metabolic pathways were predominated among the GO and KEGG pathways. Furthermore, the LC-MS/MS findings were verified by immunofluorescence. The study is the first comparative study of Kac modification associated with kidney calculi. These findings offer significant insights into the molecular mechanism underlying the formation and development of renal stones.